(untitled) (Revista Justiça do Direito, 2021)
The general objective of this research is to analyze the points in common between Brazilian Modernism and the New Latin American Constitutionalism regarding the valorization of the nativist feeling and decolonization. In methodological terms, the textual language is set via systematic reading. This is an exploratory research. It was used as a technical procedure the survey of bibliographic data, as well as statistical data, so that the research technique used is the bibliographic. Regarding the results and conclusions, it is clear that the appreciation of the native and decolonization are common aspects of the studied movements, since the first touches on the national awareness for the production of art in the country, independent of European models, and the second proposes a decolonization from the rescue of essence in actions to resist domination and exploitation and re-exist.